Clinical course, maternal and neonatal outcomes of COVID-19 infection in pregnancy: an epidemiological study in Siberia and the Far East - Tatiana E. Belokrinitskaya; Natalya V. Artymuk; Oleg S. Filippov; Nataly I. Frolova (IP Berlin A.V., 2021)
Aim. To assess the incidence, clinical course, outcomes of a novel coronavirus infection (NKI) COVID-19 for mother and child in the population of pregnant women in the Far Eastern (FEFD) and Siberian Federal Districts (SFD). Materials and methods. The study design: a population-based epidemiological prospective study. We analyzed operative information on NKI COVID-19 incidence and features of clinical course in pregnant women, women in labor and parturient women as well as maternal and perinatal outcomes for March 11 to December 25, 2020 which were provided by the FEFD and SFD chief obstetricians-gynecologists. Mathematical analysis included methods of descriptive statistics, analysis of contingency table, where the value of 2, the achieved level of significance (p) was estimated. Results. In the FEFD and SFD, over the COVID-19 2020 epidemic, the SARS-CoV-2 virus was revealed in 8485 pregnant women, women in labor and postpartum women (5.9% of pregnant women subjected to regular medical check-up; 1.71% of the sick entire population). The incidence rate in pregnant women was 3.0 times higher than in the entire population: 5933,2 vs 1960,8 per 100 thousand (p0.001). Among SARS-CoV-2 infected patients, 27.4% (2324) were asymptomatic, 52.7% (4471) have mild, 16.6% (1388) moderate, 2.5% (210) severe 0,5% (39) extremely severe clinical course. In the intensive care and anesthesiology departments, 3.57% of pregnant women and 2.24% of the entire population (p0.001) have been treated. Rate of using invasive artificial lung ventilation in pregnant women was lower than in the population: 0.48% vs 1.05% (p0.001). 27.97% (2373) of women with confirmed NKI COVID-19 completed pregnancy. 81,7% of mothers delivered on time, 18.3% prematurely. Cesarean delivery was performed in 42,0% of women, operative vaginal delivery (vacuum extraction, obstetric forceps) was registered in 0.2% of cases. 12 (0.14%) mothers died. The maternal mortality rate was 505.69 per 100 thousand live births (0.51% of patients with COVID-19 who gave birth). Mortality rates and the proportion of deaths in the entire population were statistically significantly higher: 1948.93 per 100 thousand sick population and 1.95% (p0.001), respectively. 37 (1.56%) cases of perinatal losses were registered, of which 31 (1.30%) stillbirths, 6 (0.26%) early neonatal mortality. The SARS-CoV-2 virus was revealed in 148 (6.2%) newborns with the observance of anti-epidemic measures and separation of the mother and child immediately after delivery. Conclusion. The rate of revealing SARS-CoV-2 virus in pregnant women, women in labor and parturient women in Siberia and the Far East was 3.0 times higher than in the entire population, while clinical course of infectious process was less severe (less need for invasive mechanical ventilation, lower mortality rate). In mothers with COVID-19, preterm birth rate was 3.0 times higher, caesarean delivery rate 1.4 times higher compared with the average population indicators. Reveling SARS-CoV-2 virus RNA in 6.2% of newborns suggests the possibility of vertical transmission of the infection.